Elevated presepsin Is associated with perioperative major adverse cardiovascular and cerebrovascular complications in elevated-risk patients undergoing noncardiac surgery: the leukocytes and cardiovascular perioperative events study - Handke, Jessica; Scholz, Anna; Gillmann, Hans-Jörg; Janßen, Henrike; Dehne, Sarah; Arens, Christoph; Kummer, Laura; Uhle, Florian; Weigand, Markus A.; Motsch, Johann; Larmann, Jan (Anesthesia & analgesia, 2019)
BACKGROUND:Perioperative major adverse cardiovascular and cerebrovascular events (MACCEs) are incompletely understood, and risk prediction is imprecise. Atherogenic leukocytes are crucial in cardiovascular events. However, it is unclear if surgical interventions affect leukocyte counts or activation
Gesehen am 21.08.2019